2008
DOI: 10.2337/db07-1476
|View full text |Cite|
|
Sign up to set email alerts
|

Serum FGF21 Levels Are Increased in Obesity and Are Independently Associated With the Metabolic Syndrome in Humans

Abstract: OBJECTIVE-Fibroblast growth factor 21 (FGF21) is a metabolic regulator with multiple beneficial effects on glucose homeostasis and insulin sensitivity in animal models. This study aimed to investigate the relationship between its serum levels and various cardiometabolic parameters in humans. RESEARCH DESIGN AND METHODS-A newly developedimmunoassay was used to measure serum FGF21 levels in 232 Chinese subjects recruited from our previous cross-sectional studies. The mRNA expression levels of FGF21 in the liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

85
770
15
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 822 publications
(876 citation statements)
references
References 40 publications
85
770
15
6
Order By: Relevance
“…On the contrary, there is no strict correlation between FGF21 levels and fat mass in obese patients. In particular, the association of serum FGF21 levels with BMI and fat percentage is weaker than other adipokines predominantly produced from adipose tissue, such as leptin [30] .…”
Section: Fgf21 Metabolism and Lipodystrophymentioning
confidence: 89%
“…On the contrary, there is no strict correlation between FGF21 levels and fat mass in obese patients. In particular, the association of serum FGF21 levels with BMI and fat percentage is weaker than other adipokines predominantly produced from adipose tissue, such as leptin [30] .…”
Section: Fgf21 Metabolism and Lipodystrophymentioning
confidence: 89%
“…In particular, Camporez et al showed that these improvements were associated with reduced hepatocellular triglyceride and diacylglycerol contents, decreased activation of PKCε in the liver, as well as improved insulin signaling (Camporez et al, 2013b). Interestingly, in humans, FGF21 plasma levels increase in situations of insulin resistance such as obesity, type 2 diabetes and NAFLD (Chavez et al, 2009;Dushay et al, 2010;Li et al, 2010;Zhang et al, 2008). This increase in FGF21 plasma levels may reflect a state of FGF21 resistance.…”
Section: Treatment Of Mets and Nafldmentioning
confidence: 99%
“…FGF21 regulates peroxisome proliferator-activated receptor-γ (PPAR-γ ) and the glucose-l ow ering acti vi ty of thiazolidinediones [3,4]. Despite these beneficial effects of FGF21 in glucose metabolism in animal studies, circulating FGF21 levels are often elevated in obesity, dyslipidaemia, insulin resistance, type 2 diabetes and coronary artery disease [2,[5][6][7]. The elevation in FGF21 levels may be a compensatory response to underlying metabolic stress or may be due to impaired FGF21 signalling leading to FGF21 resistance [8].…”
Section: Introductionmentioning
confidence: 99%